Story of computer: recycle or reuse computers! Help to keep the environment clean and green - Sen, Benita (New Delhi The Energy Resource Institute, 2015)
Today life can$1 (Bt be imagined without a computer. It makes accessing information and communicating across the globe possible in a few seconds. But, computers have to be used carefully. They consume energy and if improperly disposed they release toxic substances that cause pollution. The problem of e-waste is looming large on the planet. Besides, their excessive use can lead to computer addiction. The Story of Computer takes you on a journey spanning the invention of a simple abacus to the evolution of a range of hi-tech computers. It also educates you on making smart green choices when using these wonder machines!s
Keywords: Computer